2015
DOI: 10.1001/jamaoto.2015.1745
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Prognostic Factors, and Treatment of Malignant Submandibular Gland Tumors

Abstract: We report, to our knowledge, the largest study to date focused on correlates of survival in submandibular gland malignant neoplasms. Multivariate analysis found that older age at diagnosis, high tumor grade, and later stage at presentation were correlated with decreased survival whereas female sex and surgical resection were correlated with increased survival. In addition, a 3-cm tumor cutoff size was demonstrated above which was associated with a significantly less favorable prognosis. Radiation therapy had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
41
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 50 publications
(93 reference statements)
16
41
2
2
Order By: Relevance
“…However, they have a low overall incidence in the population, making their study difficult. The overall survival of the population in the current study was 66.5% at 5 years and 50.1% at 10 years, consistent with what has been previously reported in literature …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, they have a low overall incidence in the population, making their study difficult. The overall survival of the population in the current study was 66.5% at 5 years and 50.1% at 10 years, consistent with what has been previously reported in literature …”
Section: Discussionsupporting
confidence: 92%
“…Several studies support this finding. Lee et al in 2015 report in their study of submandibular gland malignancies between 1973 and 2011 obtained from the Surveillance, Epidemiology, and End Results (SEER) database that an older age bestows a hazard ratio (HR) of 1.04 (95% CI = 1.03‐1.04), female gender enjoys an HR of 0.69 (95% CI = 0.57‐0.84), and an advanced stage at presentation confers an HR of 1.56 (95% CI = 1.41‐1.72). Baddour et al in 2016 analyzed the SEER database specifically for minor salivary glands, and also showed that patients older than 65 years had worse 5‐year cause‐specific survival (HR = 1.50, 95% CI = 1.08‐2.08), and patients older than 75 years had significantly worse survival (HR = 2.88, 95% CI = 2.05‐4.06).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prevalence of histologies, our data confirm that pleomorphic adenoma (PA) is by far the most common lesion in the benign subgroup (almost 90% of cases), whereas other types are less frequently encountered . The distribution of histologies in the malignant subgroup was consistent with published data, with AdCC, AcNOS, MEC, and SDC being the most frequent tumors . The most striking difference between our study and data from the literature is the rate of high‐grade lesions.…”
Section: Discussionsupporting
confidence: 88%
“…Our series of patients included seven (14%) low‐grade, 11 (22%) intermediate grade, and 32 (64%) high‐grade lesions. An accurate grade definition, especially if three categories are identified, is not always available in previously published articles, especially for MEC, and the number of patients with an unknown tumor grade may be as high as 46.4% . This may reflect the hesitancy to excessively stratify rare tumors such as MEC, provided that in SMG the risk of failure is also relevant for low‐grade lesions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation